Radiation Safety Awareness and Practice among Radiology Staff in Kabul National Specialty Hospitals - Sahoo, Tahmina; Ahmadi, Abdul Qudoos; Amarkhil, Omran Omar (Eximia, 2023)
Background and Aim: In the world, more than ten million photographs and hundreds of thousands of nuclear medicine operations are performed daily. The exposure of such a large population even at the low dose levels used in diagnostic radiology due to definite effects and the possibility of ionizing radiation has caused public concern. This study aimed to determine the awareness of radiology staff from X-Rays adverse effects and the extent of use of safety measures in their practice in Kabul National hospitals. Methodology: A cross-sectional descriptive study was conducted among 60 radiology staff in national specialty hospitals of Kabul Afghanistan. A structured multiple-choice questionnaire was used. Data were coded and analyzed using the statistical package for social science (SPSS) software. Results: 83.3% of participants were male. 71% of the participants had >40 years old and the mean age of them was 41 years old. The type of job of participants was radiology technician. The mean of the years of job experience was 16 years. The knowledge or awareness of 95.0 % of participants was weak and 5.0% was intermediate. 96.7% of participant’s practice was good and 3.3 % was intermediate. Conclusion: The level of awareness of 95.0 % of radiology staff was very poor. This is of concern as technologists are the first point of contact with the patients and they should be adequately trained to answer common patient questions and concerns. The level of practice of 3.3 % of the staff was intermediate and 96.7% was good. Based on our results, a conscientious effort to provide a more robust education and acquire greater knowledge in these matters is required.